2011
DOI: 10.1371/journal.pone.0020341
|View full text |Cite
|
Sign up to set email alerts
|

Identification of miRs-143 and -145 that Is Associated with Bone Metastasis of Prostate Cancer and Involved in the Regulation of EMT

Abstract: The principal problem arising from prostate cancer (PCa) is its propensity to metastasize to bone. MicroRNAs (miRNAs) play a crucial role in many tumor metastases. The importance of miRNAs in bone metastasis of PCa has not been elucidated to date. We investigated whether the expression of certain miRNAs was associated with bone metastasis of PCa. We examined the miRNA expression profiles of 6 primary and 7 bone metastatic PCa samples by miRNA microarray analysis. The expression of 5 miRNAs significantly decrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
185
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 205 publications
(201 citation statements)
references
References 79 publications
14
185
0
2
Order By: Relevance
“…5). miR-143 has been shown to have an antimetastatic effect and is downregulated in several cancers (Takagi et al 2009, Kent et al 2010, Peng et al 2011. miR-143 and miR-145 are often cotranscribed and are usually investigated together as tumour suppressors (Kent et al 2014).…”
Section: :9mentioning
confidence: 99%
See 2 more Smart Citations
“…5). miR-143 has been shown to have an antimetastatic effect and is downregulated in several cancers (Takagi et al 2009, Kent et al 2010, Peng et al 2011. miR-143 and miR-145 are often cotranscribed and are usually investigated together as tumour suppressors (Kent et al 2014).…”
Section: :9mentioning
confidence: 99%
“…miR-143 and miR-145 are often cotranscribed and are usually investigated together as tumour suppressors (Kent et al 2014). In prostate cancer, over-expression of miR-143 and -145 reduces migration and invasion in vitro and tumour development and bone invasion in vivo (Peng et al 2011). Furthermore, lower expression of miR-143 and miR-145 in primary prostate cancers was significantly associated with tumour progression and the development of bone metastases (Peng et al 2011).…”
Section: :9mentioning
confidence: 99%
See 1 more Smart Citation
“…A separate study found that both miR-143 and miR-145 decreased in bone metastatic samples compared with primary tumors, and ectopic expression reduced migration, invasion and bone metastasis. 71 …”
Section: Tumor-intrinsic Mirna Regulation Of Bone Metastasismentioning
confidence: 99%
“…30 In the androgen-insensitive PC-3 prostate cancer cell line, ectopic expression of miR-143 and miR-145 prevented EMT, reducing the migratory capacities of these cells in vitro and their propensity to metastasise to bone in vivo. 31 Further, miR-145 attenuates EMT and invasion of PC-3 cells through repression of the oncogenic protein HEF1. 32 The low miR-143 and miR-145 expression levels in prostate tumours and in bone metastasis biopsies were negatively correlated to bone relapses, free prostate-specific antigen level and the Gleason score, suggesting that these miRNAs could be used as biomarkers to discriminate different stages of prostate carcinomas and predict bone metastasis relapse.…”
Section: Mirnas In Primary Carcinomas Are Potential Predictive Factormentioning
confidence: 99%